Cardioprotective effects of high-altitude adaptation in cardiac surgical patients: a retrospective cohort study with propensity score matching - Lei, Li; Liu, Mengxue; Ma, Die; Lei, Xia; Zeng, Si; Li, Peng; Huang, Keli; Lyu, Juanjuan; Lei, Qian (Frontiers in Cardiovascular Medicine, 2024)
Background: The cardioprotective effect of remote ischemia preconditioning in clinical studies is inconsistent with experimental results. Adaptation to high-altitude hypoxia has been reported to be cardioprotective in animal experiments. However, the clinical significance of the cardioprotective effect of high-altitude adaptation has not been demonstrated.Methods: A retrospective cohort study with propensity score matching was designed to compare the outcomes of cardiac surgery between highlanders and lowlanders in a tertiary teaching hospital. The data of adult cardiac surgical patients from January 2013 to December 2022, were collected for analysis. Patients with cardiopulmonary bypass and cardioplegia were divided into a low-altitude group (< 1500 m) and a high-altitude group (≥ 2500 m) based on the altitude of their place of residence.Results: Of 3020 patients, the majority (87.5%) permanently lived in low-altitude regions (495 [435, 688] m), and there were 379 patients (12.5%) in the high-altitude group (2552 [1862, 3478] m). The 377 highlander patients were matched with lowlander patients at a ratio of 1:1. The high-altitude group exhibited a 44.5% reduction in the incidence of major adverse cardiovascular events (MACEs) compared with the low-altitude group (6.6% vs 11.9%, P = 0.017). The patients in the moderate high-altitude subgroup (2500-3500 m) had the lowest incidence (5.6%) of MACEs among the subgroups. The level of creatinine kinase muscle-brain isoenzymes on the first postoperative morning was lower in the high-altitude group than in the low-altitude group (66.5 [47.9, 89.